THE RESULT OF THE QUALITY ANALYSES OF SG TYPE ROLLED SECTIONS FOR THE METAL SUPPORT OF UNDERGROUND EXCAVATIONS - Valeriu PLEŞEA; Marius Eremia VLAICU POPA; Ciprian NIMARĂ (Fiabilitate şi Durabilitate)
The quality issues of rolled sections type SG for the metal sliding fittings of supporting, was andremains a matter of real concern, having in mind that the type of steels for machining and lamination processesto which they are subject, are the causes of obtaining, whether or not the optimal technical conditions, bothduring subsequent processing of the metal elements(cutting and curving)as well, especially during the mountingand operation of service for underground. In the spirit of the promotion and adoption of suitable sttels, thispaper discusses the quality conditions which must meet, and how these factors influence the quality of the steel,and the quality of SG rolled sections manufactured in our country in terms of the elements and chemical analysisof a mechanical characteristics.